The 2017 Korean National Growth Charts for children and adolescents: development, improvement, and prospects - Jae Hyun Kim; Sungha Yun; Seung-sik Hwang; Jung Ok Shim; Hyun Wook Chae; Yeoun Joo Lee; Ji Hyuk Lee; Soon Chul Kim; Dohee Lim; Sei Won Yang; Kyungwon Oh; Jin Soo Moon (Korean Pediatric Society, 2018)
Growth charts are curves or tables that facilitate the visualization of anthropometric parameters, and are widely used as an important indicator when evaluating the growth status of children and adolescents. The latest version of the Korean National Growth Charts released in 2007 has raised concerns regarding the inclusion of data from both breastfed and formula-fed infants, higher body mass index (BMI) values in boys, and smaller 3rd percentile values in height-for-age charts. Thus, new growth charts have been developed to improve the previous version. The 2006 World Health Organization Child Growth Standards, regarded as the standard for breastfed infants and children, were introduced for children aged 0-35 months. For children and adolescents aged 3-18 years, these new growth charts include height-for-age, weight-for-age, BMI-for-age, weight-for-height, and head circumference-for-age charts, and were developed using data obtained in 1997 and 2005. Data sets and exclusion criteria were applied differently for the development of the different growth charts. BMI-for-age charts were adjusted to decrease the 95th percentile values of BMI. Criteria for obesity were simplified and defined as a BMI of ≥95th percentile for age and sex. The 3rd percentile values for height-for-age charts were also increased. Additional percentile lines (1st and 99th) and growth charts with standard deviation lines were introduced. 2017 Korean National Growth Charts are recommended for the evaluation of body size and growth of Korean children and adolescents for use in clinics and the public health sector in Korea.